Finite element of ductile/brittle plastic laminate subjected to bending and tensile load - Mohammad Hajid Bin Abidin (Nanyang Technological University, 2024)
This project involves the study of a two-layered ductile and brittle plastic laminate subjected to bending load and tensile load. Coupling effects in the ductile-brittle plastic laminate are explored when the laminate is subjected to tensile load. A Finite Element (FE) simulation using ANSYS was conducted to investigate the effects. Acrylic and polycarbonate sheets were used to stimulate the response of brittle and ductile plastic laminate respectively with five different breadth sizes – 40, 60, 80, 100, and 120mm of both acrylic and polycarbonate sheets, with fixed length and thickness of 240mm and 1mm respectively. The total thickness of the brittle/ductile laminates were fixed at 2mm. The FE results showed that displacement and stiffness increases with force and the linear and non-linear results were similar for all breadth sizes. The linear and non-linear results diverge with increasing force and an increase in breadth size reduces the divergence. Furthermore, the acrylic-polycarbonate laminate produced a bending response when subjected to a tensile load, indicating that coupling effect was present.